Răspunsuri

Cel mai inteligent răspuns!
2014-10-10T18:19:56+03:00

a)  3a + b + 6c = 39  ⇒b = 39-3a-6c = 3(13- a-2c)  și, deoarece, b=nr.prim ⇒13-a-2c =1 ⇒b=3      a+2c =12   ⇒c = (12-a)/2 = 6- a/2 a/2∈N  ⇒a=nr.par, și, singurul nr. prim, par este 2 ⇒ a=2  ⇒2c=10 ⇒c=5

b) 4a+2b+3c= 44 deoarece 4a ,2b și44 sunt nr.pare⇒3c=nr.par  ⇒ c=2   ⇒4a+2b = 38  ⇒ 2a+ b =19  ⇒ a = (19-b) /2 ⇒ b = nr. prim impar ⇒ I.   b=1  a=9∉N    II.  b=3  a= 8∉N    III. b=5 a=7  IV. b=7 a=6∉N   V. b=11  a=4∉N   VI: b=13 a=3  VII: b=17,a=1